The Utilization of Zeolite from Laundry Waste Processing as a Soil-zeolite Growing Media for Corn Plant - Maryani, Yeyen; Herayati, Herayati; Petrus, Dhannydon; Simatupang, Petrus Edison (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2024)
Laundry waste containing detergent can release large amounts of Linear Alkylbenzene Sulfonate (LAS), as an active compound, and phosphates into the groundwater. One method for solving this problem is adsorption using natural zeolite. In this study, an innovation was made to utilize zeolite resulting from the processing of laundry wastewater as a growing media with soil for corn plants. The research methodology included activation of Bayah-Banten natural zeolite, adsorption process of LAS and phosphate from laundry waste by varying the contact time (0-60 minutes) and stirring speed (150-350 rpm), analysis of LAS and phosphate content, application of zeolite, obtained from waste treatment, as a soil-zeolite growing media for corn plants, and analysis of corn morphology (stem height, stem circumference and number of leaves).The results showed that the treatment of laundry waste using the adsorption method can reduce the concentration of LAS and phosphate in wastewater. The lowest LAS concentration was obtained at a stirring speed of 300 rpm and a contact time of 60 minutes, from 0.206312 mg/L (initial LAS) to 0.13747 mg/L (final LAS). The lowest phosphate concentration was obtained at a stirring speed of 350 rpm and contact time of 60 minutes, from 0.272184 mg/L (initial phosphate) to 0.06658 mg/L (final phosphate). The application of zeolite as a growing media with a ratio of soil and zeolite of 75:25 showed a good result in the morphology of corn plants, growth in stem height of 67.74% and stem circumference of 41.67%.